Evaluating soil cover strategies for enhancing water conservation, biomass contribution, and weed control in rocoto pepper (Capsicum pubescens Ruiz & Pav.) cultivation under arid conditions - Poma-Chamana, Russell; Cama-Moreno, Elick; Flores-Marquez, Ricardo; Quello, Antony; Solórzano, Richard (Frontiers in Agronomy, 2025)
Sustainable crop production in arid regions is challenged by soil moisture loss, low organic matter content, and intense weed competition. This study aimed to assess the impact of different mulching strategies on the main crop yield, soil moisture conservation, the contribution of dry biomass and nitrogen to the soil by living covers, and the efficacy of weed control. The experiment was conducted in Santa Rita de Siguas (Arequipa, Peru) using a completely randomized block design with four treatments and three replicates. Measurements included biometric and physiological parameters of rocoto pepper (Capsicum pubescens), volumetric soil moisture, dry biomass, and nitrogen content in living covers, as well as weed density. Results indicated that most treatments had no significant impact on the biometric and physiological parameters of rocoto. Plastic mulch reduced irrigation demand and suppressed weeds, although crop yield did not significantly differ among treatments. Among the living mulches, Trifolium pratense was more effective than Melilotus albus in conserving soil moisture, maintaining levels up to 15.86%. In contrast, Melilotus albus produced the highest above-ground dry biomass (8.57 t·h−1), although both legume species accumulated similar amounts of nitrogen in their biomass. Both living covers gradually reduced weed populations, though without complete eradication. In conclusion, plastic mulch represents a potential option under conditions of severe water limitation. Meanwhile, leguminous cover crops, particularly M. albus, offer an alternative complementary strategy for enhancing soil organic matter and could promote long-term sustainability of the cropping system. These findings warrant extended temporal validation to confirm their reproducibility and reliability.